RELATIONSHIP AMONG THE ORGANIZATIONAL VARIABLES AND THE HUMAN TALENT MANAGEMENT IN RIOBAMBA´S HOSTELRIES, ECUADOR - Aldaz Hernández, Silvia Marieta (2017)
This article presents the results of the research in determining the influence degree in human management in Hostelries about sustainable tourism in Riobamba city, Ecuador. The research has quantity focus, descriptive, correlational; it is not experimental and transversal. The objectives achieved are: To related the field management processes in action in the hostelries. To show the needs that management from the sustainability view in the business competitively. It was developed 44 questionnaires to be applied with workers, employers from the hostelries. The results getting from the research through the Alpha Cronbach its value was 0.872 it is considered as good; therefore the instrument is reliable to be applied. In conclusion, there is a significant correlation according to the sample; the biggest correlation comes between the dimension of organizational culture and the organizational design with a percentage of 0.979 and the worst comes from by the knowledge and its value with a percentage of 0.102